2011
DOI: 10.1111/j.1742-4658.2011.08039.x
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of disulfide‐coupled protein folding using glutathione derivatives

Abstract: Protein folding occurs simultaneously with disulfide bond formation. In general, the in vitro folding proteins containing disulfide bond(s) is carried out in the presence of redox reagents, such as glutathione, to permit native disulfide pairing to occur. It is well known that the formation of a disulfide bond and the correct tertiary structure of a target protein are strongly affected by the redox reagent used. However, little is known concerning the role of each amino acid residue of the redox reagent, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 28 publications
2
52
0
Order By: Relevance
“…The digested peptide fragments were analyzed by HPLC (GL Science) equipped with a COSMOSIL 5C 18 -AR-II column (Nacalai Tesque) pre-equilibrated with 5% acetonitrile in 0.05% TFA and eluted with a linear acetonitrile gradient ranging from 5% to 65% at a rate of 1%/min, with detection at an absorbance of 220 nm. The molecular masses of separated peptides were determined by MALDI-TOF MS (Bruker Daltonics) (36,37). Synthetic peptides were prepared by the Fmoc (N-(9-fluorenyl)methoxycarbonyl) solid phase method, modified with AMS, and analyzed by HPLC and MALDI-TOF MS as described previously (5,34,37).…”
Section: Methodsmentioning
confidence: 99%
“…The digested peptide fragments were analyzed by HPLC (GL Science) equipped with a COSMOSIL 5C 18 -AR-II column (Nacalai Tesque) pre-equilibrated with 5% acetonitrile in 0.05% TFA and eluted with a linear acetonitrile gradient ranging from 5% to 65% at a rate of 1%/min, with detection at an absorbance of 220 nm. The molecular masses of separated peptides were determined by MALDI-TOF MS (Bruker Daltonics) (36,37). Synthetic peptides were prepared by the Fmoc (N-(9-fluorenyl)methoxycarbonyl) solid phase method, modified with AMS, and analyzed by HPLC and MALDI-TOF MS as described previously (5,34,37).…”
Section: Methodsmentioning
confidence: 99%
“…Second, refolding of the solubilized protein by the step-wise dialysis and the incubation with GSSG and L-arginine at the appropriate stage (1 M and 0.5 M of urea). The GSSG promoted formation of disulfide bonds in proteins [8] and Larginine suppressed aggregation and prevented incorrect of intramolecular disulfide bonds [9,10]. In summary, refolding procedures in this study is easy, inexpensive, time-saving and can be utilized for a high yield recovery of Fab inclusion bodies produced in E. coli.…”
Section: Resultsmentioning
confidence: 95%
“…The use of thiols containing positively charged groups has also recently been investigated by a different group working on analogs of glutathione. The Hidaka group has done extensive work with the tripeptide ArgCys-Gly (RCG) and its use as a redox buffer [184,185]. They have shown that an RCG-based buffer system resulted in a significantly higher folding recovery of lysozyme as compared to glutathione.…”
Section: Folding Of Synthetic Polypeptide Chainsmentioning
confidence: 99%